Bedford Glossary of Critical & Literary terms - Murfin ,Ross (Bedford Books, 1998)
Engaging, authoritative, and affordably priced, "The Bedford Glossary" is a comprehensive reference that clearly and accessibly defines hundreds of important literary and critical terms from classical times to the present, making them real and relevant to twenty-first century students through examples uniquely drawn from contemporary literary and popular culture.